Investigating the learning value of early clinical exposure among undergraduate medical students in Dubai: a convergent mixed methods study - Al-Jayyousi, Reem; Abu Mahfouz, Nour; Otaki, Farah; Paulus, Agnes; Czabanowska, Katarzyna; Zaman, Qamar; AlAshkar, Masa; Stanley, Adrian; Kilian, Paddy (BMC medical education, 2025)
Introduction The benefits of Early Clinical Exposure (ECE) in medical education are often stated but there is limited evidence on how to effectively maximize its learning value. The challenge for medical educators lies in finding ways to enhance the quality of ECE in alignment with students’ feedback, while realizing the learning outcomes. The purpose of this study is to investigate undergraduate medical students’ perception of an innovative ECE intervention in Dubai, United Arab Emirates, developed using design-based research in alignment with adult, experiential learning theories. Methods A convergent mixed methods study design was utilized. The data was collected using a tailormade survey to solicit both quantitative and qualitative feedback. Quantitative data was analyzed using SPSS. Qualitative data analysis was inductive based on constructivist epistemology. Following the conclusion of the independent data analyses of the quantitative and qualitative datasets, the primary inferences were integrated using the iterative joint display analysis process. Results Out of the 68 students who attended the ECE, 54 responded. The percentage of the total extent of agreement that the ECE: familiarized them with learning in the clinical environment and brought forth the institutional values were 79.60% and 86.43%, respectively. The extent of active engagement and self-directed learning, with a mean of 6.80(2.42), was significantly associated with how much the learners reaped from the learning experience (P < 0.05). A novel conceptual model, namely: ‘Early Clinical Exposure Added Value’, with five interconnected themes, was developed from the qualitative analysis. Integration of findings led to six meta-inferences: Embeddedness in context of learning, System perspective, Patient-centricity, Theory–practice link, Resilience, and Proactiveness. Conclusion The more medical students engage in their learning, the more ECE contributes to building their academic resilience, and propels them in terms of clinical correlations, skills’ development, and values reinforcement. Securing engagement opportunities for the learners, when designing and planning for the ECE, is essential. Optimizing the ECE learning value can happen systematically through continuously developing the respective intervention in alignment with the principles of design-based research and anchoring it in constructivism experiential learning theories.